Tax Farming Redux: Experimental Evidence on Performance Pay for Tax Collectors. (1st October 2015) - Khan, Adnan Q.; Khwaja, Asim I.; Olken, Benjamin A.
Abstract: Performance pay for tax collectors has the potential to raise revenues, but might come at a cost if it increases the bargaining power of tax collectors vis-à-vis taxpayers. We report the first large-scale field experiment on these issues, where we experimentally allocated 482 property tax units in Punjab, Pakistan, into one of three performance pay schemes or a control. After two years, incentivized units had 9.4 log points higher revenue than controls, which translates to a 46% higher growth rate. The scheme that rewarded purely on revenue did best, increasing revenue by 12.9 log points (64% higher growth rate), with little penalty for customer satisfaction and assessment accuracy compared to the two other schemes that explicitly also rewarded these dimensions. The revenue gains accrue from a small number of properties becoming taxed at their true value, which is substantially more than they had been taxed at previously. The majority of properties in incentivized areas in fact pay no more taxes, but instead report higher bribes. The results are consistent with a collusive setting in which performance pay increases collectors' bargaining power over taxpayers, who have to either pay higher bribes to avoid being reassessed or pay substantially higher taxes if collusion breaks down.